Transcriptional activation of the mouse Mx gene by type I interferon. - Staeheli, P (1986)
Mouse cells of the Mx+ genotype accumulate Mx mRNA in response to type I interferon (IFN). Nuclear runoff experiments show that IFN stringently regulates Mx gene expression at the level of transcription. Mx mRNA synthesis peaks about 3 h after IFN treatment, and within 5 h, Mx mRNA concentration rises from undetectable levels to about 0.1% of polyadenylated RNA.